Abraomas Kulvietis at the University of Siena: Unveiling his Doctoral Record - Pociūtė, Dainora (Literatūra, 2025)
The article publishes, for the first time, the complete text of the doctoral record of Abraomas Kulvietis (Abraham Culvensis, d. 1545), accompanied by its Latin transcription and Lithuanian translation. Kulvietis, a pioneer of Lithuanian literacy and the Reformation in Lithuania, received his doctorate in both laws (in utroque iure) at the University of Siena on November 29, 1540. He was the only Lithuanian student at this Italian university during the sixteenth century.The research discusses the details and historical circumstances of the document preserved in the archive of the Archdiocese of Siena (Archivio Arcivescovile di Siena), which complements the biography of this outstanding early modern Lithuanian humanist and sheds light on his intellectual environment at the University of Siena.
Keywords: Early Modern Era; Abraomas Kulvietis (Abraham Culvensis); University of Siena; Legal Studies; Doctoral Records; Philo-Protestantism